2019
DOI: 10.1111/1751-7915.13483
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a rapeseed meal fermentation model for iturin A production by Bacillus amyloliquefaciens CX‐20

Abstract: Summary Iturin A is an important broad‐spectrum antifungal cyclic lipopeptide used as an ideal potential biological control agent. However, its application is limited mainly due to the producer strains’ low productivity and the high production costs. Here, a potentially industrial strain Bacillus amyloliquefaciens CX‐20 was proved to use low‐cost rapeseed meal (RSM) as the sole source of all nutrients except the carbon source for the high productivity of iturin A. A fermentation model was first established to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…Iturin A is an important antifungal cyclic lipopeptide with wide application prospects. In previous studies, we verified the advantages of direct bio-utilization of untreated RSM for effective iturin A production by Bacillus in submerged fermentation, which compared favourably with commercial nitrogen sources (Jin et al, 2014(Jin et al, , 2015Chen et al, 2019a). Moreover, the potential industrial strain B. amyloliquefaciens CX-20 was able to achieve high iturin A productivity by directly using RSM for all nutrients except for the carbon source (Chen et al, 2019a).…”
Section: Introductionsupporting
confidence: 63%
See 3 more Smart Citations
“…Iturin A is an important antifungal cyclic lipopeptide with wide application prospects. In previous studies, we verified the advantages of direct bio-utilization of untreated RSM for effective iturin A production by Bacillus in submerged fermentation, which compared favourably with commercial nitrogen sources (Jin et al, 2014(Jin et al, , 2015Chen et al, 2019a). Moreover, the potential industrial strain B. amyloliquefaciens CX-20 was able to achieve high iturin A productivity by directly using RSM for all nutrients except for the carbon source (Chen et al, 2019a).…”
Section: Introductionsupporting
confidence: 63%
“…(2014) and Chen et al . (2019a), which demonstrated that almost no iturin A were produced when 8 g l −1 ammonium nitrate was used as the nitrogen source. However, when an equal amount of ammonium nitrate was added into RSM medium, the yield of iturin A reached 1.07 g l −1 in spite of the negative effects of ammonium nitrate (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Iturin A was extracted according to a reported method [4, 5, 24]. Briefly, 0.3 mL of the mixed fermentation broth was added into a 2 mL glass tube containing 1.2 mL of methanol, shaken well and incubated for 60 min.…”
Section: Methodsmentioning
confidence: 99%